KARAKTERISTIK PAPAN SEMEN PARTIKEL DARI LIMBAH PABRIK KUAS - Amalia Amalia; Muhtarom Riyadi (Jurnal Poli-Teknologi, 2016)
ABSTRACT This study aims to investigate the properties of cement particle board from brush factory waste using Portland Puzzolan Cement (PPC) as adhesive. Characteristics of cement particle board was studied consists of: density, heavy boards, thickness swelling, water absorption, flexural strength and modulus of elasticity. the test object is made with 4 variations in the amount of PPC, namely: 1 waste: 1 PPC, 1 waste: 1.5 PPC, 1 waste: 2 PPC, 1 waste: 3 PPC. The results showed that (1) weight of cement board average was 10.60 kg/m2-12,89 kg/m2, (2) Based on the density, cement particle board with brush factory waste included in the category of high-quality cement boards, (3) water absorption 12,45%-24,98 %, (4) thickness swelling 2,24% - 4,39 %, (5) flexural strength 40,26 kg/cm2 - 45,56 kg/cm2, and (6) modulus of elasticity 1302,46 kg/cm2 - 1642,18 kg/cm2. The cement particle board with brush factory waste for all compositions meet the standard of wood wool cement boards (SNI 03-2104-1991). The best Characteristics of cement particle board with brush factory waste is 1 waste : 2 PPC. Keywords: cement particle board, brush factory waste, portland pozzolan cement, cement board characteristics ABSTRAK Penelitian ini bertujuan untuk meneliti karakteristik papan semen partikel dari limbah pabrik kuas dengan perekat jenis Portland Puzzolan Cement (PPC). Karakteristik papan semen partikel yang diteliti terdiri dari: kerapatan, berat papan, pengembangan tebal, daya serap air, kuat lentur dan modulus elastisitas. Benda uji papan semen partikel dibuat dengan ukuran 30 cm x 30 cm x 1 cm. Penelitian ini menggunakan empat variasi perbandingan antara jumlah limbah pabrik kuas dengan perekat PPC, yaitu: 1limbah : 1 PPC, 1 limbah : 1,5 PPC, 1 limbah : 2 PPC, dan 1 limbah : 3 PPC. Kata kunci : papan semen partikel, limbah pabrik kuas, portland puzzolan cement, karakteristik papan semen